Working Towards Education Success Using Data: A review of Ghana's journey towards improved learning outcomes using data - Radford, Kate; Ampofo, Rudolph (EdTech Hub, 2024)
The sub-Saharan Africa region is trapped in a learning crisis with devastating implications for children. The Covid-19 pandemic further exacerbated the situation, with children losing an estimated equivalent of an additional year’s learning. Not addressing the regional learning crisis will have a detrimental impact on economic development and well-being and risks restricting future national and regional economic growth and productivity and fuelling social unrest. Education research has shown that good quality education system data, when judiciously used, can support improved learning outcomes among a host of other positive impacts on national education systems. This case study is the first in a series documenting the journey of Ghana’s Ministry of Education towards the effective use of data to guide its decision-making for policy and practice. Keywords: data for decision making; data governance; data management; Ghana; education data systems; evidence-based policy An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13766685 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1059 ZenodoArchiveConcept: 13766684
Keywords: _r:AddedByMyEducationEvidence

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
ZenodoArchiveID: 5652063 previousDOI: 10.5281/zenodo.4430545 previousZenodoArchiveID: 4430545 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4430545 10.5281/zenodo.5652063 2339240:94IZR4ET 2339240:TST2YB8H 2405685:3BWKQDYQ 2405685:FEXGB4IJ 2405685:ZGYUEEZQ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Teacher Deployment in Sierra Leone: Lessons learnt and going forward - Beoku-Betts, Iman (EdTech Hub, 2023)
This report provides an overview of the teacher deployment process in Sierra Leone prior to and including 2022. Through interviews with key stakeholders in the Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC), we look at lessons learnt from the deployment process and next steps for how teacher deployment can be implemented. Although there are a number of volunteer teachers in Sierra Leone, the TSC are aiming to increase the number of qualified teachers on the government payroll as well as retaining teachers in rural areas. It was noted that teachers from rural areas being put on the government payroll and deployed to rural schools are better placed to teach in rural schools than teachers moving from urban to rural areas. Hpwever, it is still challenging to find qualified teachers in these rural areas. The TSC want to look at how they can target teachers to take up rural positions, either through distance learning to gain the right qualifications or working with teacher training institutions (TTIs) to prioritise schools in rural areas for placement. Overall, the TSC want to use data as the basis for decision-making on deploying teachers equitably. Keywords Teacher deployment; teacher training; unqualified teachers; volunteer teachers; rural schools; data for decision-making An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7521062 ZenodoArchiveConcept: 7521061 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7521062 10.53832/edtechhub.0145 2405685:M3D6NGR4 2405685:WVRHTVIZ 2486141:V94NMZIU
Keywords: _r:AddedByZotZen

Investigating the Activity Levels of School Quality Assurance Officers in Sierra Leone - Beoku-Betts, Iman; Leh Wi Lan (EdTech Hub, 2023)
Since the launch of the Free Quality School Education (FQSE) Programme in 2018, the Sierra Leone Ministry of Basic and Senior Secondary Education (MBSSE) has prioritised the use of data for decision-making across several education reform programmes. Part of this vision has been to build systems to measure school quality through School Quality Assurance Officers (SQAOs) using data collection and feedback. This system includes using tools for teacher management, lesson observations, school improvement, and attendance monitoring. This report presents findings from qualitative research conducted in three districts in Sierra Leone. The aim is to provide the MBSSE and other partners with insights to understand the variation in and what is needed to maximise SQAO activity levels, increase principal engagement with digital tools, and support and promote quality visits to schools. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7521375 ZenodoArchiveConcept: 7521374 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7521375 10.53832/edtechhub.0154 2405685:AHVWDNGT
Keywords: _r:AddedByZotZen

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

The Future of EMIS: A Public Financial Management Perspective - Cresswell, Simon; Long, Cathal; Fraser, Alasdair (EdTech Hub, 2023)
Policymakers in low- and lower-middle-income countries are in a bind: while more complex EMIS designs may make processes more likely to fail following donor exit, simple EMIS designs do not provide enough information to track the effects of reforms and progress addressing the learning crisis. Even for basic measures, EMIS appear to generate inaccurate data in many cases. Reflections on EMIS implementation challenges point to demand and supply issues, with the former being the more important determinant for realising EMIS potential and their ongoing development. This paper considers demand and supply for EMIS from a public financial management (PFM) perspective. Keywords: public financial management, budgeting, digital, data governance, education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7335773 ZenodoArchiveConcept: 7335772 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7299806 10.5281/zenodo.7335773 10.53832/edtechhub.0165 2339240:LJTXPKUD 2405685:4NSU75DR 2405685:ABK6ZFI8 2405685:PFKAMFI6
Keywords: _r:AddedByZotZen

Remote Supervision Options for School Quality Assurance Officers: Recommendations for a cost-effective and rapid develop-and-test process - Beoku-Betts, Iman; Ampofo, Rudolph; Haßler, Björn (EdTech Hub, 2024)
The Sierra Leone Secondary Education Improvement Programme II (SSEIP II) is a five-year programme funded by the UK Foreign, Commonwealth and Development Office (FCDO) to support the Ministry of Basic and Senior Secondary Education (MBSSE) to improve learning outcomes for students at secondary level and to increase the enrolment, retention and well-being of girls and children with disabilities in school. Part of the programme includes exploring the use of different digital tools for School Quality Assurance Officers (SQAOs), including tools for remote visits. In December 2022, the EdTech Hub collaborated with the Government of Sierra Leone and implementing partners of the Leh Wi Lan programme (continued under SSEIP II) to better understand what factors affect the variability in the activity levels of SQAOs and the level of engagement with digital tools by school principals. Based on the findings of this research, the SSEIP II project will look at supporting the MBSSE to formalise remote supervision options for the SQAOs, particularly for those with remote clusters. As part of this work, this report focuses on recommendations for how SQAOs can conduct remote school visits, particularly for schools in hard-to-reach areas.An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10354009 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1002 ZenodoArchiveConcept: 10354008
Keywords: _r:AddedByMyEducationEvidence

Using EdTech to Support Effective Data Monitoring: A Curated Resource List. - Koomar, Saalim; Blest, Harriet (EdTech Hub, 2020)
This list curates resources on the use of EdTech to support the effective monitoring of educational outcomes, such as learning, reporting, and attendance. Resources shared are both tools and initiatives that can be adapted to support effective educational monitoring.
ZenodoArchiveID: 4762325 previousDOI: 10.5281/zenodo.4762325 PREV_DOI_NOT_ETH: 10.5281/zenodo.4091396 shortDOI: 10/ghgng6 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3407517 10.5281/zenodo.4762325 10/ghgng6 2339240:C9LP4Y2Z 2339240:EKNZDSVU 2339240:GMJF38V5 2339240:MZKWF23D 2339240:QJX4VXGR 2405685:7I4HVAV2 2405685:884LRL46 2405685:ANHT4I3J 2405685:FS4CMYUB 2405685:RV39YP9Q 2405685:WCYEVIJU 4656463:K7HMFX7H
Keywords: C:Mozambique; ES:Educational data; ES:Monitoring and evaluation; F: Helpdesk response; L:Low-level foundational skills; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted

Monitoring Distance Education: A Brief to Support Decision-Making in Bangladesh and Other Low- and Lower-Middle-Income Countries - Kaye, Tom; Groeneveld, Caspar; Bashir, Amreen (EdTech Hub, 2020)
This brief outlines a model for monitoring and evaluating distance learning based on a desktop review of interventions during the Covid-19 school closures and other previous school shutdowns. It then examines how this might be applied in the Bangladeshi context.
ZenodoArchiveID: 5652092 previousDOI: 10.5281/zenodo.4140104 previousZenodoArchiveID: 4140104 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4140104 10.5281/zenodo.4140104 10.5281/zenodo.4140104; 10.5281/zenodo.5652092 2339240:2K6FG2CF 2339240:2XJTN3MP 2339240:3TNWACL9 2339240:942WVA7N 2339240:DN7NQV5Y 2339240:LKQW3A8S 2339240:MDTPARWA 2339240:PNTVB7PY 2339240:U3838PXA 2339240:XIE9NJ3S 2405685:5DNJGPNU 2405685:BA3K6CK8 2405685:BLRKEEAU 2405685:CCZW4ARW 2405685:DAFBBJ3F 2405685:DP9HJGLT 2405685:HRT8E6US 2405685:RVIEHPP5 2405685:XUVA9827 2405685:Z6UIK8CZ 2405685:ZITF5IDK 2534379:FDZIF5DH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No INSPIRE recid found

EdTech for Contexts of Forced Displacement: A Rapid Evidence Review - Barnes, Katrina; Katrin, L (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices for learners in contexts of forced displacement. The main aim of the review is to provide education decision-makers, funders, and implementers (among others), with a clear picture of which interventions may be the most effective in these contexts and, crucially, which implementation decisions facilitate or hinder this effectiveness. We reviewed evidence generated between 2019 and 2024 on EdTech implementations in different contexts of forced displacement. We focused on implementations aimed at primary- and secondary-age learners, as well as their teachers and caregivers. Keywords: forced displacement, refugee education, education in emergencies An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14622107 ZenodoArchiveConcept: 14622106 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1085 2405685:KIEIX7NP
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11197419 ZenodoArchiveConcept: 11197418 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1027 10.53832/edtechhub.1028 2405685:DQ9GNC3J 2405685:M6A4ZHJ3
Keywords: _r:AddedByMyEducationEvidence

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7065183 ZenodoArchiveConcept: 7065182 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7065183 10.53832/edtechhub.0142 2339240:HPTMF4RJ 2405685:2437EGZU 2405685:UCMLR25N
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Afzal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15366685 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1113 ZenodoArchiveConcept: 15366684
Keywords: _r:AddedByMyEducationEvidence

Shifting Power Dynamics in Education Decision-Making: Investigating the role of a matching algorithm to improve teacher deployment in Sierra Leone - Godwin, Katie; Cameron, Emma; Frazer, Madleen Madina; Dube, Gugulethu; Mackintosh, Alisdair; Koutecký, Tomáš; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15039164 ZenodoArchiveConcept: 15039163 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1103 2405685:IRFH43RX 2405685:SFNCI64Z 2486141:C9Q4ZDTR
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

EdTech for Learners With Cognitive and Learning Disabilities: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Afzal, Nimra (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with cognitive and learning disabilities. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. We discuss the nature of EdTech for learners living with cognitive and learning disabilities, the effectiveness of these initiatives, and barriers for accessing EdTech. The RER aims neither to advocate nor discourage the use of technology to support education for learners with coginitive and learning disabilities, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; cognitive disabilities; learning disabilities; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10987889 ZenodoArchiveConcept: 10987888 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1006 10.53832/edtechhub.1023 2339240:U7UE5PIN 2405685:B422KBGQ 2405685:PGRMI8NH
Keywords: _r:AddedByMyEducationEvidence; ⛔ No INSPIRE recid found

Summary: EdTech in Vietnam - A Rapid Scan - Honda, Delanie; Halla, Ken; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
This document is a summary of a country scan on XYZ produced by EdTech Hub as part of the ASEAN-UK SAGE programme. EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Vietnam. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12818950 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1041 ZenodoArchiveConcept: 12818949
Keywords: _r:AddedByMyEducationEvidence

Randomised Controlled Trial Protocol: Digital personalised learning to improve literacy and numeracy outcomes in Kenyan classrooms - Major, Louis; Daltry, Rebecca; Otieno, Mary; Otieno, Kevin; Zhao, Annette; Hinks, Jessica; Sun, Chen; Friedburg, Aidan (EdTech Hub, 2023)
This protocol provides a detailed overview of a cluster-randomised controlled trial (RCT) being undertaken in pre-primary schools in Kenya. The RCT seeks to rigorously investigate the impact of a classroom-integrated digital personalised learning (DPL) tool on early grade numeracy and literacy learning outcomes. The protocol is being disseminated prior to endline data analysis to promote transparency and a comprehensive understanding of the RCT approach and design. This protocol was originally published in October 2023. This is an updated version where we have a) clarified that the sample size stated in Sections 2 and 2.2 is the 'pre-attrition' sample; and b) added a paragraph to Section 2.4.1 to provide further clarification regarding the use of code-switching. No changes to the analytical approach have been made. Keywords: digital personalised learning; DPL; Randomised controlled trial; RCT; research methodology; learning outcomes; Kenya An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8354887 ZenodoArchiveConcept: 8354886 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8354887 10.53832/edtechhub.0176 2405685:JNH4277Z
Keywords: _r:AddedByZotZen

A Literature Overview of Accountability and EdTech: Recommendations for Using Technology to Improve Accountability in Educational Systems from Ghana and Other LMICs. - McIntyre, Nora; Sabates, Ricardo; Eberhardt, Molly Jamieson (EdTech Hub, 2021)
ZenodoArchiveID: 4575561 PreviousDOI: 10.5281/zenodo.4468852 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4575561 2339240:DTA9GETP 2339240:V8PHTCMI 2405685:5TQ3YM2R 2405685:AI9EYM2F 2405685:E5W5QCIE
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

EdTech in Nigeria: A Rapid Scan. An overview of EdTech policies and interventions in Nigeria with a focus on northern Nigeria - Ramesh Vasudevan, Sharanya; Oyedele, Oluwatomisin (EdTech Hub, 2024)
Commissioned as a Helpdesk request from the FCDO-funded Partnership for Learning for All in Nigeria (PLANE) project, this EdTech Hub rapid scan provides an overview of the EdTech landscape in Nigeria. Given the PLANE programme’s focus on northern Nigeria, this rapid scan also assesses state-level policies and infrastructural challenges in three northern Nigerian states — Jigawa, Kaduna, and Kano. Furthermore, this rapid scan builds on the evidence presented in the previous EdTech Hub rapid scan from 2020, which focused on all states and the situation before the Covid-19 pandemic. Keywords: EdTech; policies; interventions; northern Nigeria; Partnership for Learning for All in Nigeria An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11235144 ZenodoArchiveConcept: 11235143 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1029 10.53832/edtechhub.1030
Keywords: _r:AddedByMyEducationEvidence

Rapid Evidence Review on Remote Teaching and Learning - Pacitto, Julia; Hayat, Amal; Hinks, Jessica; Emerusenge, Aime Parfait; Ullah, Noor; Rabi, Asma (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to teaching practices and pedagogies for emergency remote learning. The main aim of this review is to provide education decision-makers, funders, and implementers (among others) with a clear understanding of the available global evidence on effective practices in teaching when students are educated remotely during emergencies, and to assess the relevance of this evidence for low- and middle-income contexts. The findings of the RER are organised by the following five themes: (i) instructional design for remote learning in emergency contexts; (ii) student engagement and interactivity in emergency remote teaching; (iii) assessment, feedback, and pedagogical adaptation in remote teaching during emergencies; (iv) well-being, ‘Maslow before Bloom’, and pedagogies of care in emergency remote teaching; (v) teacher training and support in remote teaching during crises. It also identifies critical gaps in the literature on emergency remote teaching and learning, and suggest avenues for future productive research to address these gaps. Keywords: Education in Emergencies, remote learning, pedagogy, teaching methods, EdTech, emergency remote teaching An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14967648 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1098 ZenodoArchiveConcept: 14967647
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

EdTech in Lao People's Democratic Republic: A Rapid Scan - Afzal, Nimra; Thang, Sarah; Tulivuori, Jukka; Thinley, Sangay; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive. Nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, and in this case, Lao People’s Democratic Republic (PDR). This report was originally written in February 2024. It is based primarily on desk research, with quality assurance provided by a country expert based at the Australian Council for Educational Research. Keywords: Ministry of Education and Sports; digital skills; training programmes; government expenditure; learning outcomes; disparities An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11118414 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1026 ZenodoArchiveConcept: 11118413
Keywords: _r:AddedByMyEducationEvidence

Cost-Effective EdTech Paper 1: A position piece on how the sector can make progress - Mitchell, Joel; D'Rozario, Jonny (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7003826 ZenodoArchiveConcept: 7003825 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7003826 10.53832/edtechhub.0118 2339240:3XB6YUXL 2405685:GXLAGDUM 2405685:RPR47JXT 2405685:ZXBB58KS
Keywords: _r:AddedByZotZen

Cost-Effective EdTech Paper 2: Good practice - Mitchell, Joel; D'Rozario, Jonny (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7106003 ZenodoArchiveConcept: 7106002 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7106003 10.53832/edtechhub.0119 2405685:Y3SBIPF9 2405685:ZVX4DTXQ
Keywords: _r:AddedByZotZen

What Should Ministries of Education Prioritise When Crafting Their Edtech Strategies? - Thinley, Sangay (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at priorities for governments and ministries of education when crafting EdTech Strategies. Interest in developing EdTech strategies related to operational targets and outcomes has increased over the past few years, especially in response to the learning disruptions caused by the Covid-19 pandemic. Evidence suggests that countries with established EdTech strategies were better equipped to respond to the pandemic and its effects due to their advanced preparation and readiness for large-scale remote learning. We examine the key principles for EdTech strategies, including the importance of focusing on learning outcomes, inclusivity, teacher training, costs, and contextual needs, among other factors. We draw on EdTech Hub's work in supporting several governments in designing and implementing EdTech strategies, as well as broader evidence from the field, to offer practical insights. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt, such as prioritising consultative processes of strategy development while focusing on multi-modal, problem-driven EdTech solutions and interventions guided by a unifying educational goal. We highlight areas that require further research, in particular questions related to cost-effective approaches to improving global learning, how governments can develop dynamic and iterative strategies, and the role of private sector partnerships in the successful implementation of EdTech strategies. Keywords: EdTech; education technology; education strategy; best practices for EdTech; EdTech planning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13360175 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1054 ZenodoArchiveConcept: 13360174
Keywords: _r:AddedByMyEducationEvidence

From algorithm outputs to classroom impact: A conversation with Marian Abu, director of teacher management at the Teaching Service Commission - Frazer, Madleen Madina (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14266292 ZenodoArchiveConcept: 14266291 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1080 2405685:AUFN9TP4 2405685:WIB4DE6R 2486141:TQ3SZHVM
Keywords: _EdTechHub_Output; _r:AddedByMyEducationEvidence

Understanding the Potential of Using EdTech to Measure and Mitigate Learning Losses in Latin America and the Caribbean - Wyss, Natalie; Myers, Christina (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and the Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in December 2021. The UNICEF team requested a resource that summarises what is known about the use of technology and other approaches to measure and mitigate learning losses related to Covid-19 impacts on education in the LAC region. This resource aims to support UNICEF country offices and partners in the LAC region to assess learning losses and inform school reopening and the development of hybrid education strategies. Our research found that there are limited EdTech approaches to measuring and mitigating learning losses, and fewer still that are specific to the LAC region. This piece outlines the following: What is understood about learning losses and how they can be quantified; What common guidance and evidence suggest are the most effective ways to mitigate Covid-19-specific learning losses; How established EdTech tools and non-tech-based approaches can be leveraged and applied to both processes. Keywords: learning losses; school reopening; personalised learning; assessment; remedial education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7023358 ZenodoArchiveConcept: 7023357 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7023358 10.53832/edtechhub.0110 2405685:FUBDMTM8
Keywords: _r:AddedByZotZen

Sandbox Handbook V.2.0 - EdTech Hub (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7019219 ZenodoArchiveConcept: 7019218 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7019219 10.53832/edtechhub.0108 2339240:LNQBY8R8 2405685:49ZFP7UN 2405685:MP7LCGPN
Keywords: _r:AddedByZotZen

Designing Teacher Learning Circles for Improved Foundational Numeracy Outcomes: Findings from the National Numeracy Programme in Malawi - Correa de Oliveira, André; Plaut, Daniel; Kanyoza, Charity; Boilo, Violet; Chidothi, Emmanuel; Kadzamira, Esme; Mpoola, Dorothy; McBurnie, Chris; Phiri, Magret; Haßler, Björn (EdTech Hub, 2024)
The Malawi National Numeracy Programme (NNP) was designed in 2020 in partnership with the Malawi Ministry of Education and Cambridge Education (Mott McDonald), funded by the UK Foreign, Commonwealth and Development Office (FCDO). Building on findings from a prior qualitative review of the NNP's programme components, EdTech Hub proposed a new phase of design-based implementation research (DBIR) to be undertaken in Term 2 of the 2022–2023 school year to refine the school-based teacher continuous professional development (TCPD) model of the NNP. As part of the research, EdTech Hub developed a new TLC guide to be tested in schools. Through observations, focus group discussions, and interviews, the Hub gathered teacher feedback and used it to co-design and iterate on this guide alongside teachers. This report summarises the principal findings from the study. It also outlines the research background, methodology, findings, and recommendations for the programme moving forward. Keywords: teacher continuous professional development, teacher learning circles, National Numeracy Programme (NNP), Malawi, design-based implementation research An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7568301 ZenodoArchiveConcept: 7568300 KerkoCite.ItemAlsoKnownAs: 2129771:VEW2PXA5 10.5281/zenodo.7568301 10.53832/edtechhub.0177 2405685:2AN8XVIA
Keywords: _r:AddedByZotZen

Education Sector Analysis. Assessing the enabling environment for gender equality - Republic of Sierra Leone (UNICEF, IIEP - UNESCO, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:X5MR76ZW 2405685:29U93GQF

2021 Annual School Census Final Report - Ministry of Basic and Senior Secondary Education, Sierra Leone (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:M7XYZTWF 2405685:C7C3BM9Z